RUSSIA TODAY: ECONOMY, FINANCE, SOCIETY - Kulikov, Nikolay; Kulikov, Alexey; Kulikova, Maria; Nazarchuk, Natalia (Revista Inclusiones, 2020)
As crisis in the Russian economy, finance and society grows, the causes of it become more obvious. Nowadays this topic gains great relevance and importance. The main objective is to reveal the factors causing the crisis phenomena in the economy. The major tasks were focused in accordance with the set objectives to reveal the main factors and ways of overcoming the economic downfall in Russia. The instrumentation includes the methods such as analysis of scientific base, as well as synthesis of the obtained data into theoretical conclusions and practical recommendations. Methodological and theoretical basis includes scientific works of Russian and foreign scholars. Russian economy in 2015 and 2016 is characterized by emerging crisis phenomena. The article presents the assess of the performance of the financial bloc of the government and the Central Bank, reviews and suggests a new alternative economic and financial policy in Russia, stimulating consumer demand of the population and investment activity of both business and population that will lead to economic growth.